Cognitive decline in older adults with type 2 diabetes: Unraveling site-specific glycoproteomic alterations - Yishai Levin; Nili Tickotsky; David Morgenstern; Hila Wolf-Levy; Barak Markus; Itzik Cooper; Anat Reiner-Benaim; Jaime Uribarri; Ron Unger; Aron S. Buchman; Michal Schnaider Beeri (PLoS ONE, 2025)
Type 2 diabetes (T2D) is consistently related to an increased risk of cognitive decline and dementia. However, the molecular underpinnings of this association remain poorly understood. In this study, we applied a novel mass spectrometry-based glycoproteomic methodology to profile serum glycoproteins in older adults with T2D, aiming to identify glycopeptiforms associated with cognitive impairment. Our method allowed comprehensive profiling of N glycosylation in addition to the unique ability to profile glycation events on specific amino acid sites. Serum samples from initially cognitively normal older adults with T2D were collected, with participants classified as cognitive decliners (who developed impairment) and non-decliners (who maintained normal cognition over time). We identified significant differences in the abundance of glycopeptiforms between these groups, noting that certain glycopeptiforms exhibited unique changes over time in decliners. We identified 13 glycopeptiforms that exhibited significant differences between the groups both at baseline and in their rates of change over time. Pathway analysis indicated that glycation events were linked to metabolic pathways while glycosylation to immune-related pathways, aligning with established links between these processes and cognitive decline. This study offers new insights into glycoproteoform alterations in older adults with T2D experiencing cognitive decline. It highlights the potential of specific glycopeptiforms as biomarkers for early cognitive impairment in T2D. Further validation in larger cohorts will enhance our understanding of glycosylation and glycation in T2D and potentially lead to the discovery of novel treatment targets for T2D-related cognitive decline. Raw data and search are available via ProteomeXchange with identifier PXD050780.